2021
DOI: 10.1136/bmjopen-2020-045596
|View full text |Cite
|
Sign up to set email alerts
|

How digital health solutions align with the roles and functions that support hospital to home transitions for older adults: a rapid review study protocol

Abstract: IntroductionOlder adults may experience challenges during the hospital to home transitions that could be mitigated by digital health solutions. However, to promote adoption in practice and realise benefits, there is a need to specify how digital health solutions contribute to hospital to home transitions, particularly pertinent in this era of social distancing. This rapid review will: (1) elucidate the various roles and functions that have been developed to support hospital to home transitions of care, (2) ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 94 publications
0
30
0
Order By: Relevance
“…A rapid review was deemed appropriate, given the need to generate timely recommendations for future digital health interventions, as the COVID-19 pandemic has prompted an immediate need for novel technological supports [ 21 , 50 , 51 ]. Consistent with prior studies that conducted a secondary analysis of reviews [ 52 - 54 ], a secondary analysis entailed reexamining relevant data to answer different research questions and addressing knowledge gaps identified in the initial review [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A rapid review was deemed appropriate, given the need to generate timely recommendations for future digital health interventions, as the COVID-19 pandemic has prompted an immediate need for novel technological supports [ 21 , 50 , 51 ]. Consistent with prior studies that conducted a secondary analysis of reviews [ 52 - 54 ], a secondary analysis entailed reexamining relevant data to answer different research questions and addressing knowledge gaps identified in the initial review [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the remainder of this section, we outline the specific steps undertaken to complete the review. As this secondary analysis aimed to answer different research questions than intended within the published protocol, the methods used in this study necessitated some deviations from the original protocol, as described in the following sections [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations